Corporate culture as a factor in company development - Liu Yunshan (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
The object of the research is the corporate culture management system of BYD. The subject of the research is the theory, methods, and practices of corporate culture management at BYD, particularly how cultural development and management can enhance the company’s competitiveness and employee cohesion. The purpose of the qualifying Master's thesis is to provide a theoretical justification for the foundations of BYD's corporate culture management, to reveal the current state, challenges, and future prospects of BYD's corporate culture, and to offer directions for improvement by drawing on the successful experiences of foreign companies in corporate culture management. Based on the results of the research some suggestions for the improvement of BYD's corporate culture management system have been given, including both theoretical analysis and practical suggestions. The obtained results can be used as a reference for BYD and other enterprises in building and improving the corporate culture management mechanism, and promote the sustainable competitiveness of enterprises in the global market.
Scientific advisor: Cherniavska I., PhD in economics, associate professor, department management, business and professional communications
Keywords: SOCIAL SCIENCES::Social sciences; management; corporate culture of the company; corporate culture of the company; personnel management; management models; value orientations of employees; company development